The needs analysis of archaebacteria and eubacteria web-based biology learning media - Maulida Ulfa Hidayah; Sonja V.T. Lumowa; Didimus Tanah Boleng (JPBIO (Jurnal Pendidikan Biologi), 2020)
The media used in learning archaebacteria and eubacteria are very varied, but there are still obstacles in the delivery of subject matter, so it is necessary that the formulation of media developed. The purpose of this research was to analyze the needs of developing web-based biology learning media on archaebacteria and eubacteria material for students of X-grade high school. The research sample was determined by a purposive sampling technique considering school status, conditions, school facilities, and students' characteristics. There are 3 samples of schools, namely 2 public schools and 1 private school in Balikpapan city. The research data were collected using observation and interview guidelines, the research data were also analyzed descriptively and quantitatively. The conclusions of this study: 1) the use of learning media as a teaching resource in the biology learning process that occurs in the field has not been carried out optimally; 2) archaebacteria and eubacteria material is difficult material; 3) Learning media that need to be developed on archaebacteria and eubacteria material is web-based media, namely multimedia that combines learning resources in the form of text, images, animation, practice questions, glossaries, sounds, and videos equipped with back sounds and captions.Keywords: Needs analysis, media learning, web-based, archaebacteria, eubacteria